Power Loss Reduction in the Active Distribution Network by Doubly Fed Induction Generator (DFIG) Placement and Sizing Using Ordinary Particle Swarm Optimization (PSO) and an hybrid of Genetic Algorithm (GA) and PSO (HGAPSO) - Musau, Peter Moses; Abungu, Nicodemus Odero (My University, 2013)
Due to the increased importance of DFIGs in optimization of real and reactive power losses and the maintenance of voltage profile, the general methods of DG placement and sizing in the existing literature cannot be of practical importance in DFIG .In this paper a pure PSO method used in general DG is compared with a HGAPSO in the siting and sizing of DFIG with the objective of minimizing power losses .The corresponding Combined participation factors are assigned using the DFIG Domain Distributed Slack Bus Model and a comparison made on the two schemes of loss minimization. The obtained results for the real and reactive power losses and voltage voltage profile illustrate the DFIG need in the modern power system.
Keywords: Distributed Generator (DG); Doubly Fed Induction generator (DFIG); Hybrid GAPSO (HGAPSO); Genetic Algorithm(GA); Particle Swarm Optimisation (PSO)